2001
DOI: 10.1038/ng713
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SEPN1 cause congenital muscular dystrophy with spinal rigidity and restrictive respiratory syndrome

Abstract: One form of congenital muscular dystrophy, rigid spine syndrome (MIM 602771), is a rare neuromuscular disorder characterized by early rigidity of the spine and respiratory insufficiency. A locus on 1p35-36 (RSMD1) was recently found to segregate with rigid spine muscular dystrophy 1 (ref. 1). Here we refine the locus and find evidence of linkage disequilibrium associated with SEPN1, which encodes the recently described selenoprotein N (ref. 2). Our identification and analysis of mutations in SEPN1 is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
225
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(230 citation statements)
references
References 12 publications
4
225
0
1
Order By: Relevance
“…rigid spine Cmd Pathogenesis rigid spine syndrome CMD is characterized by marked limitation in the flexion of the spine, gradual development of scoliosis leading to reduced respiratory vital capacity and respiratory failure as well as joints contractures. In 2001, Moghadaszadeh et al 9 identified the sePN1 gene and several mutations resulting in rigid spine CMD, suggesting that selenoprotein N can be involved in redox reactions into the cell, protecting it from oxidant damage. Petit et al 186 demonstrated that sePN1 is a glycoprotein-localized within the endoplasmic reticulum that is more abundant in human fetal tissues than in adult ones, including skeletal muscle.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…rigid spine Cmd Pathogenesis rigid spine syndrome CMD is characterized by marked limitation in the flexion of the spine, gradual development of scoliosis leading to reduced respiratory vital capacity and respiratory failure as well as joints contractures. In 2001, Moghadaszadeh et al 9 identified the sePN1 gene and several mutations resulting in rigid spine CMD, suggesting that selenoprotein N can be involved in redox reactions into the cell, protecting it from oxidant damage. Petit et al 186 demonstrated that sePN1 is a glycoprotein-localized within the endoplasmic reticulum that is more abundant in human fetal tissues than in adult ones, including skeletal muscle.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Genetic deficiency of selenoprotein N (SePN) in humans results in rigid spine muscular dystrophy, multiminicore disease, or desmin-related myopathy with Mallory body-like inclusions (45,46). To date, SePN is the only selenoprotein known to be involved in a human genetic disorder, but no targeted mutation in mice has been reported and mechanistic details of its function are missing.…”
Section: Other Selenoproteinsmentioning
confidence: 99%
“…These include rigid-spine muscular dystrophy, multiminicore disease, and Mallory body-like desmin-related myopathy, and are collectively referred to as SEPN-related myopathies. Several pathologic SEPN1 mutations within the coding region and the 5ЈUTR, and also within the SECIS element (discussed earlier), have been identified in patients with SEPN-related myopathies (105,230). However, the underlying molecular mechanisms behind the SelN-dependent myopathies are poorly understood because the functional characterization of this protein is lagging behind.…”
Section: F Selenoprotein Nmentioning
confidence: 99%
“…SelN is the only selenoprotein so far directly linked to a disease (230,265), and unlike the other selenoproteins, its characterization started with a known loss-of-function phenotype. Several forms of early-onset myopathies characterized by hypotonia, weakness, axial muscle impairment, spinal rigidity and life-threatening respiratory failure have been linked to the SelN gene (SEPN1) locus (265).…”
Section: F Selenoprotein Nmentioning
confidence: 99%